2015
DOI: 10.14735/amko2015321
|View full text |Cite
|
Sign up to set email alerts
|

Combining Systemic Therapies with Radiation in Non-small Cell Lung Cancer

Abstract: SummaryRadiotherapy has been the mainstay of treatment of stage III non-small cell lung cancer patients. In the early 90s, combined treatment with chemotherapy was introduced. In 1995, a meta-analysis showed improved treatment outcome of the sequential use of cisplatin-based chemotherapy and radiotherapy compared to radiotherapy alone. Subsequent randomized studies and two meta-analyses demonstrated that concurrent radiochemotherapy is superior (local control and overall survival) to sequential usage of both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…By morphological type, lung cancer is primarily divided into small cell lung cancer (SCLC) and non-SCLC (NSCLC) (2). Lung cancer cells are sensitive to radiotherapy, and thoracic radiotherapy can eradicate chemotherapy-resistant tumor cells (3,4). A retrospective study demonstrated that clinical outcomes following stereotactic body radiotherapy are equal or superior to surgery alone for overall survival in patients with stage I-II NSCLC (3).…”
Section: Introductionmentioning
confidence: 99%
“…By morphological type, lung cancer is primarily divided into small cell lung cancer (SCLC) and non-SCLC (NSCLC) (2). Lung cancer cells are sensitive to radiotherapy, and thoracic radiotherapy can eradicate chemotherapy-resistant tumor cells (3,4). A retrospective study demonstrated that clinical outcomes following stereotactic body radiotherapy are equal or superior to surgery alone for overall survival in patients with stage I-II NSCLC (3).…”
Section: Introductionmentioning
confidence: 99%